Impact of Glass Fiber Content and Packing Pressure on Weld Line Integrity in Injection Molded Short Glass Fibre Reinforced Polyamide (2024)
Managing the challenge of weld lines of short-fiber reinforced polymers (SFRPs) in injection molding is crucial for enhancing the mechanical performance of these composites. This study evaluates the impact of various glass fiber contents (0 to 50 wt%) within a polyamide 6 (PA6) matrix on the tensile and flexural properties at weld lines, comparing each sample to its counterpart without a weld line. Our findings indicate that weld lines have minimal impact on the mechanical properties of composites with low fiber content (10 wt%). However, at higher fiber contents, the strength, modulus, and strain at fracture are significantly reduced due to unfavorable fiber orientations at the weld lines. Increasing the packing pressure during injection molding can partially recover these properties by promoting favorable fiber orientation at the weld line. This signifies the importance of carefully controlling processing parameters to optimize the mechanical performance of SFRPs at weld lines.